Active games for increasing social and emotional competencies of young adults in probation system: a one-sample trial study in Izmir city in Turkiye - Inci Derya Yucel; Gorkem Yararbas (BMC Psychology)
Abstract Introduction The prevalence of substance use among young adults has been increasing in Turkiye. Probation as a form of execution continues to grow in popularity around the world, as it has the potential for more successful outcomes than closed institutional execution methods. However, in the face of changing societal and individual needs, the probation system must rapidly adapt to current public realities, especially with new approaches, including the use of purposeful physical movement for young adults who are obliged due to illegal substance use. These competencies are the ability to regulate emotions, manage social relationships, and make responsible decisions. Objective It aims to implement active games, including physical activities, that support the social and emotional competencies of individuals in probation sentence. Methods This study presents the results of a pilot program held in Turkiye under an Erasmus + Key Action 3 project entitled Active Games for Change (AG4C), which includes a range of innovative face-to-face active games that were specifically created and designed to support the development of identified social emotional competencies in a probation directorate that serves young adult offenders. The study was carried out with 50 young adult offenders. The Collaborative for Academic, Social, and Emotional Learning (CASEL) model, which defines five social and emotional skills (self-awareness, self-management, responsible decision making, relationship skills, social awareness), was used to support observation and game design. The present study involved the codesign of a total of 18 active games to develop these five competencies. Results There was a significant difference between the scores at baseline and the mental wellbeing total and self-awareness scores of the offender individuals after the ActiveGames4Change intervention who had been exposed to the ActiveGames4Change program. The results, based on a two-tailed test, support the conclusion that the intervention had a significant impact on performance scores (from 1 to 3), which were collected from the educators across the nine assessed time points. Conclusion This research has demonstrated that active games can play a particular and deliberate role not only in physical activity but also in developing social-emotional competencies in young individuals in probation settings in the justice system. Trial registration This trial is retrospectively registered online at ClinicalTrials.gov with the identifier NCT06737744.